The kingdom of speech - Wolfe, Tom (Little, Brown and Company, 2016)
"Taking readers on a rollicking ride through history, a master storyteller and reporter, whose legend began in journalism, presents a paradigm-shifting argument that speech, not evolution, is responsible for humanity's complex societies and achievements,"--NoveList.